Pharmacological Treatment for Acute Traumatic Musculoskeletal Pain in Athletes - Alessandro de Sire (MDPI AG, 2021)
Pain management is a crucial issue for athletes who train and compete at the highest performance levels. There are still evidence gaps for the use of analgesics for sports injuries despite the growing interest in training and competition settings. However, high-quality research is needed to determine the most appropriate and optimal timing and formulations in non-steroidal anti-inflammatory drug and opioid management, particularly given the strictness of anti-doping regulations. Indeed, the role of pharmacological therapy in reducing acute traumatic pain in athletes should still be addressed to minimize the timing of return to sport. Therefore, the aim of this comprehensive review was to summarize the current evidence about pain management in the setting of acute injury in elite athletes, providing the most informed strategy for pain relief and performance recovery.